Pancasila Values Were Forgotten In The Formation Of Indonesian Legislation - Supeno, Bambang Joyo; Widyorini, Sri Retno (Jurnal Ilmiah Dunia Hukum, 2024)
the ideology of the Indonesian nation, is considered to have been neglected in the formation of legislation. As is known, Pancasila, as the source of all sources of state law, is interpreted as the principles or foundation for thinking and acting in the formation and enforcement of legislation. Empirically, the values of Pancasila have been forgotten as principles, both in abstracto and in concreto, leading to deviations, disharmony, and inconsistency in the formation of legislation. This study is a qualitative research using a normative juridical approach, which will explore and analyze these issues using secondary data and purposive random sampling. The analysis results show that three factors influence the neglect of Pancasila values as "principles" and the inconsistency in the use of "principles" provisions in the formation of legislation: the fluctuating disintegration of the Pancasila curriculum, the unclear and non-explicit regulation of Pancasila values as "principles" in Law No. 12 of 2011 juncto Law No. 13 of 2022 and its implementing regulations, and the inconsistency in the use of "principles" provisions in legislation. Based on these issues, it is necessary to strengthen the Pancasila curriculum, amend Article 2 by adding the phrase "Pancasila values as the principles of the content of legislation," and require the political will of the government and legislature to strengthen the curriculum and regulations for the formation of legislation.